New species of Langona Simon, 1901 and Neaetha Simon, 1884 (Araneae: Salticidae) from Thailand - Żabka, Marek; Patoleta, Barbara M. (Zootaxa, 2020)
The genera Langona Simon, 1901 and Neaetha Simon, 1884 are recorded from Thailand. Langona pattayensis sp. nov. (♂♀) and Neaetha wesolowskae sp. nov. (♂♀) are described and diagnosed. Distributional maps and remarks on the relationships of both genera and species are provided.